ENHANCING ELEMENTARY STUDENT’S KNOWLEDGE THROUGH WEB SECURITY FUNDAMENTALS COUNSELING - Ahmad Sanmorino; Rendra Gustriansyah; Shinta Puspasari (Universitas Muhammadiyah Mataram, 2024)
Abstract: This Community Service Program (PkM) focuses on delivering fundamental web security concepts tailored to the age-specific needs of young learners. Collaborative efforts among teachers, and parents, ensure a cohesive implementation of web security measures within the school environment. This PkM activity aims to enhance elementary school student's knowledge about the importance of web security. The method used is by giving lectures and interactive discussions to PkM participants. The total number of participants involved in this PkM is around 25 people, consisting of teachers and students. Evaluation of this PkM activities based on questionnaire feedback from PkM participants. According to feedback from participants, there has been a noticeable improvement in understanding the significance of web security. Before engaging in PkM activities, only approximately 5 percent of students possessed knowledge regarding the importance of web security. However, post-PkM activities, approximately 90 percent of students affirmed their awareness of the significance of web security.